EFFORTS TO DEVELOP CHARACTER VALUES THROUGH THE DISCOVERY OF THE BOJONGMENJE TEMPLE SITE - Andres M. Ginting; Asnewastri; Ahmad Fakhri Hutauruk; Krissi Wahyuni Saragih; Juliardi Damanik; Yohannes Setiawan Zega (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2025)
This article describes a historical discovery of the Bojongmenje Temple Site which should provide a forum for the formation of the character of the local community, considering that a history must have cultural values. The purpose of this article is to examine efforts to build character values around the Bojongmenje temple discovery site. These results indicate that the discovery of the Bojongmenje Temple site does not have a significant impact on the formation of the character values of the local community. The many efforts that have been made by the management have not been able to make everyone care about taking the side of the historical values of the Bojongmenje site. As values in society are starting to fade, it will be interesting to see if a discovery site can change its current character. Overall, this is an interesting point for further research by identifying the causes of deficient character formation.